NATO and missile defence: Implications for Germany before the Bucharest summit in 2008 - Alexander Bitter (Stiftung Wissenschaft und Politik (SWP), 2007)
At the NATO summit in Bucharest at the end of April 2008, one of the issues the Alliance will deal with is the question of missile defence for Europe. Within the framework of its missile defence programme, the United States want to station ten interceptors in Poland and a radar in the Czech Republic. According to the indications of the American government those elements could protect 75 percent of European territory. A decision on the way ahead would be of fundamental importance for the general strategic direction taken by the Alliance. In the emotionally-charged public discussion, one extremely relevant aspect has not received much attention. Missile defence touches on the core of the original reason for the existence of NATO: the protection of the Alliance area and its inhabitants from harm. If Germany should come within the range of regimes equipped with weapons of mass destruction, and if military action by the international community against these regimes became necessary, Germany's strategic situation would change radically.The central question of this analysis is what options the European members of NATO have in view of the rapid development of the American programme. In addition, proposals for a possible European contribution, a command-structure and a decision-making process involving the Europeans, are considered. The research paper comes to the conclusion that accepting Washington's offer and progressive involvement in missile defence would bring justifiable, quite low technological risks. The project would also fall within an acceptable financial envelope, and be accompanied by an enormous increase in military capabilities for NATO. (SWP Research Papers)
Keywords: 320